Evaluations of the Psychometric Properties of the Recovery-Stress Questionnaire for Athletes among a Sample of Young French Table Tennis Players. Issue 2 (April 2014) - Martinent, Guillaume; Decret, Jean-Claude; Filaire, Edith; Isoard-Gautheur, Sandrine; Ferrand, Claude
This study used confirmatory factor analyses (CFAs) among a sample of young French table tennis players to test: (a) original 19-factor structure, (b) 14-factor structure recently suggested in literature, and (c) hierarchical factor structure of the Recovery-Stress Questionnaire for Athletes (RESTQ–Sport). 148 table tennis players completed the RESTQ–Sport and other self-report questionnaires between one to five occasions with a delay of 1 mo. between each completion. Results of CFAs showed: (a) evidence for relative superiority of the original model in comparison to an alternative model recently proposed in literature, (b) a good fit of the data for the 67-item 17-factor model of the RESTQ–Sport, and (c) an acceptable fit of the data for the hierarchical model of the RESTQ–Sport. Correlations between RESTQ–Sport subscales and burnout and motivation subscales also provided evidence for criterion-related validity of the RESTQ–Sport. This study provided support for reliability and validity of the RESTQ–Sport.